2018
DOI: 10.1002/2017jd027360
|View full text |Cite
|
Sign up to set email alerts
|

Using Cell‐Phone Tower Signals for Detecting the Precursors of Fog

Abstract: In the last decade, published research has indicated the potential of commercial microwave links that comprise the data transmission infrastructure of cellular communication networks as an environmental monitoring technology. Different weather phenomena cause interference in the wireless communication links that can therefore essentially act as a low‐cost sensor network, already deployed worldwide, for atmospheric monitoring. In this study we focus on the attenuation effect caused in commercial microwave netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…So, naturally, only those links that intersect with fog help with its detection. Commercial communication signals have proved viable for monitoring temperature inversion and humidity by considering the attenuation caused by the atmospheric refractive index (David and Gao 2018 ). Prior research has demonstrated that the sensitivity of detecting fog increases if the frequency of signals is high and the links are tiny, which is the current demand in high population urban areas, making it suitable both for communication and detection purposes.…”
Section: Fog Forecasting and Detectionmentioning
confidence: 99%
“…So, naturally, only those links that intersect with fog help with its detection. Commercial communication signals have proved viable for monitoring temperature inversion and humidity by considering the attenuation caused by the atmospheric refractive index (David and Gao 2018 ). Prior research has demonstrated that the sensitivity of detecting fog increases if the frequency of signals is high and the links are tiny, which is the current demand in high population urban areas, making it suitable both for communication and detection purposes.…”
Section: Fog Forecasting and Detectionmentioning
confidence: 99%
“…Attenuation of MWL signal can be from sources other than rainfall. For instance, variations in water vapour content and air temperature [60,61], strong solar irradiance and multipath propagation can all cause RSL attenuation even in clear sky conditions [30]. Therefore, to estimate R from RSL data, it is essential first to identify the rain periods (wet periods, i.e., when rain is present on the MWL path) in the RSL data and separate them from the no rain periods (dry periods, i.e., when rain is absent on the MWL path).…”
Section: Wet/dry Classification Of Rsl Datamentioning
confidence: 99%
“…Nevertheless, the lack of accuracy of this technology when measuring at ground level can be introduced as a limitation, since this region is criti-cal in the case of inversions for extreme air pollution events [45]. Finally, some publications can be outlined [16,17,[46][47][48] where the characterization of the effects of thermal inversion by means of its impact on cellular networks is analyzed. In this regard, it is important to highlight that these types of structures were not properly designed for developing this work of monitoring.…”
Section: Methodsmentioning
confidence: 99%